2021
DOI: 10.1002/er.6625
|View full text |Cite
|
Sign up to set email alerts
|

Nano enhanced fluids and latent heat storage material for photovoltaic modules: A case study and parametric analysis

Abstract: Thermal stress causes reduction in the open circuit voltage of photovoltaic (PV) modules which results in a reduction in overall power generation. Photovoltaic thermal (PV/T) collectors have been used to mitigate this issue by providing both cooling of the cell temperature and yielding thermal energy in the same space. However, the implementation of PV/T systems in the industry is still lacking and requires further innovative solutions to achieve higher electrical and thermal efficiencies. In this article, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The result showed that the prepared nanocomposite PCM is stable, and CuO nanoparticles enhance the TC by 118.87% at a nanoparticle concentration of 3%. A parametric analysis of nano‐enhanced PCM and nanofluids for photovoltaic thermal (PVT) systems was performed along with a case study by Sopian et al 20 The result showed a peak and overall efficiencies of PVT systems 61.6% and 77.8%, respectively. Xiong et al 21 performed a study on thermal property improvement of nitrate salts using 20 nm silica nanoparticles and reported that potassium nitrate salts showed an excellent improvement in TC and specific heat than sodium nitrate salts.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the prepared nanocomposite PCM is stable, and CuO nanoparticles enhance the TC by 118.87% at a nanoparticle concentration of 3%. A parametric analysis of nano‐enhanced PCM and nanofluids for photovoltaic thermal (PVT) systems was performed along with a case study by Sopian et al 20 The result showed a peak and overall efficiencies of PVT systems 61.6% and 77.8%, respectively. Xiong et al 21 performed a study on thermal property improvement of nitrate salts using 20 nm silica nanoparticles and reported that potassium nitrate salts showed an excellent improvement in TC and specific heat than sodium nitrate salts.…”
Section: Introductionmentioning
confidence: 99%
“…The energy transfer rate of 0.3% mass fraction Al 2 O 3 nano-additives-based stearic acid NEPCM was observed to be higher than 11.08% than the stearic acid-based TES system. Sopian et al 24 carried out the experimental and parametric analysis on a photovoltaic thermal collectors system with nano-PCM and nanofluid as the heat transfer fluid. Results revealed that the average and peak overall photovoltaic thermal efficiencies had been improved, and also the electrical efficiency of the photovoltaic thermal was higher than photovoltaic.…”
Section: Introductionmentioning
confidence: 99%
“…9 Such a disadvantage increases PCM's melting time and creates a hightemperature zone near the heat source with nonuniform temperature distribution. To improve the thermal performance of PCM, a composite of PCM with nanoparticles, 10 fins, 11 or foam 12 has been proposed by researchers.…”
mentioning
confidence: 99%